SEMIOTIC ANALYSIS OF THE LYRICS OF THE SONG "UNTUK KITA RENUNGKAN" BY EBIET G. ADE - Ulina, Trinity Dew; Syamsiah, Khoirunnisa Nur; Adwam, Urfiyani (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2024)
This study examines the meaning in the lyrics of the song "Untuk Kita Renungkan" by Ebiet G. Ade. The researcher uses Roland Barthes' theory of semiotic analysis which contain three kinds of meanings: denotation, connotation, and myth. Roland Barthes' semiotic theory is applied to explain the three interpretations of the song lyrics. The methodology used in this study is inductive reasoning, which is a process from thinking things that are specific to things that are general. Data is collected by searching for documents containing the required information from various sources. The analysis of the song lyrics "Untuk Kita Renungkan" from a semiotic perspective yields the following findings. The denotative meaning in the song lyrics "Untuk Kita Renungkan" revolves around self-reflection and life, emphasizing the importance of good preparation and self-awareness and self-control in the journey of life. Additionally, the song also has a connotative meaning about the importance of self-introspection, learning from past experiences, having strong determination and spirit to face every challenge in life. The song does not specifically discuss myths but focuses more on the message about the importance of reflecting on the meaning of life's journey in order to live a better life.